Proxy caching algorithm based on segment popularity for mobile streaming media - YANG Ge1; LIAO Jian-xin1; ZHU Xiao-min1; YANG Bo1; HUANG Hai1 (Tongxin xuebao)
A novel dynamic scheduling algorithm P2CAS2M2（proxy caching algorithm based on segment popularity for mobile streaming media）based on segment popularity for mobile streaming media was proposed.Proxy caching admis-sion and replacement algorithm based on the object segment popularity for mobile streaming media was implemented.The principle was obeyed that the data cached for each mobile streaming media object were in proportion to their popu-larity at the proxy server.The cache window size was updated periodically according to the average access time of the clients.Simulation results show that this algorithm is more adaptive than A2LS（adaptive and lazy segmentation algorithm） for the variety of the proxy server cache.It can gain more average number of cached mobile streaming media objects and less delayed requested ratio while byte-hit ratio of P2CAS2M2 is close to or exceeds A2LS under the circumstance of the same proxy cache space.